lnter-civilizational Relations and the Destiny of the West.: Dialogue or Confrontation? Studies in World Peace Vol. 7 - Kadankavil, Thomas (Journal of Dharma, 1999)
Victor Segesvary, lnter-civilizational Relations and the Destiny of the West. Dialogue or Confrontation? Studies in World Peace Vol. 7, Lewiston, Queenstown, Lampeter: The ’Edwin Mellen Press, 1998 pp, Viii+354. (ISBN 0-7734-8327-6).